Prevention of War: A Scoping Review on Primary Preventive Measures in Public Health - Tessa-Maria Brake; Oliver Razum (Public Health Reviews, 2024)
Objectives: Wars and armed conflicts have a major impact on population health. As the discipline of public health aims to increase the health at population level, professionals play a significant role in dealing with war and armed conflict. There is need for research on prevention. This study aims to map the literature on existing public health approaches addressing the primary prevention of war and/or armed conflict.Methods: We performed a scoping review in the databases Web of Science, PubMed and Google Scholar, followed by a narrative synthesis.Results: We included 15 studies. We identified three main themes regarding preventive measures: 1) research on root causes of conflicts, surveillance and documentation of its health consequences; 2) education and awareness raising on the consequences of conflicts; and 3) interventions to change socio-economic and political conditions conducive to conflicts.Conclusion: A two-tiered conceptual framework emerges: For primary prevention of war, public health should promote human rights and the rule of law. To prevent armed conflict within states, public health should address the social determinants of health and aim to reduce poverty and inequity.